Community schools in the Philippines and their implications for Iran - Abolfotouh, Zahra Mahin Dokht 1930- (1964)
A detailed presentation of the policies and practices of the community schools in the Philippines was made in this study and from which, implications on the primary schools in Iran were deduced.
Thesis (M.Ed.)--University of the Philippines
Keywords: Community and school